PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MELALUI STRATEGI BELAJAR PQ4R UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS MATERI POKOK KEGIATAN EKONOMI KELAS VII-A SMP NEGERI 1 ASEMBAGUS SEMESTER GENAP - Siti Seituni (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
PQ4R learning strategy was used to help students remember what they read. The purpose of this study was to enhance student’s learning activity and learning outcomes by implement PQ4R learning strategy in social science subject with economic activities topic class VII-A State Junior High School 1 Asembagus on 2013/2014 academic year. The research object were students of class VII-A as many as 22 students. This research design was Classroom Action Research with Hopkins model using four phases: planning, action, observation and reflection. To obtain the data, this study used observation, interviews and tests. The data analysis used qualitative descriptive analysis. As a result, learning activity observations showed that student’s learning activity reached 85,98% on the first cycle, and the learning activity observation result on the second cycle reached 87.88%. While student’s learning outcomes on the first cycle has reached 86.36%, but the implementation on the second cycle was better than the first cycle. So, it can be concluded that the implementation of PQ4R learning strategy can enhance student’s learning activity and learning outcomes in social science subject with Economic Activity topic class VII-A State Junior High School 1 Asembagus.